2013
DOI: 10.1002/pat.3173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyol structure on the properties of the resultant magnetic polyurethane elastomer nanocomposites

Abstract: In this study, two types of magnetic polyurethane (PU) elastomer nanocomposites using polycaprolactone (PCL) and polytetramethylene glycol (PTMG) as polyols were synthesized by incorporating thiodiglycolic acid surface modified Fe 3 O 4 nanoparticles (TSM-Fe 3 O 4 ) into PU matrices through in situ polymerization method. TSM-Fe 3 O 4 nanoparticles were prepared using in situ coprecipitation method in alkali media and were characterized by X-ray diffraction, Fourier Transform Infrared Spectrophotometer, Transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Incorporation of Fe 3 O 4 magnetic nanoparticles into organic polymer matrices to fabricate organic-inorganic nanocomposites has attracted considerable attention in many areas, such as biomedical implants and devices, drug delivery, electromagnetic interference shielding (EMI), water purification, magnetic shape memory polymers (MSMP) [9]. Polyurethane as organic matrix is highly favored because of several advantages such as excellent mechanical properties, chemical stability, blood and tissue compatibility and particularly, low cost products [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of Fe 3 O 4 magnetic nanoparticles into organic polymer matrices to fabricate organic-inorganic nanocomposites has attracted considerable attention in many areas, such as biomedical implants and devices, drug delivery, electromagnetic interference shielding (EMI), water purification, magnetic shape memory polymers (MSMP) [9]. Polyurethane as organic matrix is highly favored because of several advantages such as excellent mechanical properties, chemical stability, blood and tissue compatibility and particularly, low cost products [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The COC asymmetric and symmetric stretching vibrations of PCL are observed at 1231 and 1157 cm −1 , respectively. The absorption bands at 1098 and 1038 cm −1 are also assigned to asymmetric and symmetric COC stretching vibrations of urethane groups . All the FTIR spectra confirm the formation of a polyurethane structure.…”
Section: Resultsmentioning
confidence: 64%
“…In this investigation, NCO‐terminated polyurethane prepolymer was synthesized according to a recommended procedure . For this purpose, appropriate amounts of IPDI and previously degassed PCL (with a mole ratio of 2:1) were reacted by step growth polymerization in a three‐necked flask equipped with reflux condenser, mechanical stirrer, heating oil bath, dropping funnel and nitrogen inlet and outlet.…”
Section: Methodsmentioning
confidence: 99%
“…For better dispersion of nanoparticles, their surfaces were somewhat (non)covalently modified in order to improve their miscibility with the polymer matrix and create nanoscale netpoints in the polymer matrix. Surface modification of Fe 3 O 4 nanoparticles could improve their compatibility with polymer matrix and result in uniform dispersion in the matrix . OA is one of the most widely used kinds of surfactants to modify Fe 3 O 4 nanoparticles due to its high affinity with Fe 3 O 4 nanoparticles .…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification of Fe 3 O 4 nanoparticles could improve their compatibility with polymer matrix and result in uniform dispersion in the matrix. 39 OA is one of the most widely used kinds of surfactants to modify Fe 3 O 4 nanoparticles due to its high affinity with Fe 3 O 4 nanoparticles. 35,40 It was reported that OA could form a single layer or bi-layers coated structures on the surface of Fe 3 O 4 nanoparticles.…”
Section: Surface Modification Of Fe 3 O 4 Magnetic Nanoparticlesmentioning
confidence: 99%